Frontispiece: Topotactic Synthesis of Porous Cobalt Ferrite Platelets from a Layered Double Hydroxide Precursor and Their Application in Oxidation Catalysis. Issue 51 (12th September 2017) - Ortega, Klaus Friedel; Anke, Sven; Salamon, Soma; Özcan, Fatih; Heese, Justus; Andronescu, Corina; Landers, Joachim; Wende, Heiko; Schuhmann, Wolfgang; Muhler, Martin; Lunkenbein, Thomas; Behrens, Malte
Abstract : Holey hexagonal platelets of cobalt ferrite, CoFe2 O4, can be obtained by co‐precipitation and thermal decomposition of a layered double hydroxide (LDH) precursor. These particles are single crystalline and porous at the same time and show a topotactic relationship with the precursor. They are active as catalyst in alcohol oxidation and as electrocatalyst in the oxygen evolution reaction showing a clearly different behavior than commercial powder likely due to their unique microstructure. For more details, see the Communcation by T. Lunkenbein, M. Behrens et al. onpage 12443 ff. Lunkenbein, Behrens et al. on #topotactic transformation of layered double hydroxides to ferrite spinel